Mechanical Properties and Microstructure of Artificial Bone Prototype Made of Bovine Bone Powder by Mixing Method - Paskarino, Rio; Affi, Jon; , Gunawarman (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
The purpose of this study is to obtain bovine bone powder with high content calcium-phosphorus coumpound through combination of ball milling and heating processes. These processes was carried out in four stages at a temperature of 800°C for heating process. The obtained powder was then mixed with zirconia and resin, and then molded into a metal mold to obtain artificial bone prototypes in the form of dog-bone tensile test specimen. The tensile test was then conducted to the specimens to obtain the strength and strain capacity of the artificial bones. Fractured specimen surface morphology and sample microstructure were then examined using a scanning electron microscope (SEM) equipped with Energy Dispersive X-ray (EDX). The result of this study shows that the highest levels of calcium and phosphorus contents is 35.07% and 19.04%, respectively, with powder fineness of 63 ?m. The strength of artificial bone varies according to the powder volume fraction, where the fraction of 90% powder and 10% resin gives the strength 5,57MPa. While the fractions of 80-20, 70-30 and 60-40 give the strength of 11.84 MPa, 13.66 MPa, and 9,56 MPa, respectively. The microstructure of the specimens shows micro cracks, voids, detachement particles, and agglomeration with different extent depend on the fraction of the powders.